Reducing radiation hazard opportunities in neonatal unit: quality improvement in radiation safety practices. Issue 2 (21st October 2017) - Edison, Priyantha; Chang, Pi Sun; Toh, Guan Hong; Lee, Li Na; Sanamandra, Sarat Kumar; Shah, Varsha Atul
Abstract : Aim: Guided by the ALARA - "As Low As Reasonably Achievable" principle in radiation safety, a quality improvement project to optimise the bedside diagnostic imaging process to the best standards of care was conducted over a six month period. The goal was too reduce the radiation hazard opportunities in the neonatal intensive care unit by at least 75% from the existing level at Q2/2015, within 6 months. Methods: The existing bedside imaging process was critically analysed and the following quality improvement initiatives were implemented namely, mandatory lead protective gear to healthcare staff, gonadal shield for neonates, guidelines for optimal collimation of X-ray beam and optimal positioning of neonates. Radiation dosimetry results, regular staff awareness sessions and strong collaboration between neonatologists, radiologists, radiographers and neonatal nurses helped to ensure compliance to the revised imaging process. Radiation hazard opportunities were measured by analysing all radiographs done during the period under baby exposure and healthcare staff exposure categories. Summary of results: Radiation hazard opportunities were reduced by 100% to healthcare staff and 75% to neonates, and the overall reduction was 83%. The rate of discordance between radiograph request forms and images taken was measured as a surrogate marker for compliance to the project initiatives and it declined by 77%. Mandatory orientation of staff to the revised policy on the standardised diagnostic imaging process, regular radiation awareness talks and staff feedback sessions are among several measures taken to sustain the project.